The Rainbow Vertex-Connection Number of Star Fan Graphs - Bustan, Ariestha Widyastuty; Salman, A.N.M. (CAUCHY, 2018)
A vertex-colored graph  is said to be rainbow vertex-connected, if for every two vertices  and  in , there exists a  path with all internal vertices have distinct colors. The rainbow vertex connection number of , denoted by is the smallest number of colors needed to make  rainbow vertex connected. In this paper, we determine the rainbow vertex connection number of star fan graphs.